Prevalence of Insulin Resistance in Urban Indian School Children Who Are Overweight/Obese: A Cross-Sectional Study - Das, Rashmi Ranjan; Mangaraj, Manaswini; Nayak, Saurav; Satapathy, Amit Kumar; Mahapatro, Samarendra; Goyal, Jagdish Prasad (Frontiers in Medicine, 2021)
Background: Limited data are available for insulin resistance (IR) in children with over-weight/obesity from Indian subcontinent. Identifying predictors of IR in this population is important, as they may be used as a screening tool for future metabolic complications. Materials & Methods: This school based cross-sectional study was conducted in an Eastern Indian city. Anthropometry and blood pressure measurements were carried out as per the published guidelines. Venous blood samples were taken in a fasting state to measure plasma glucose, insulin, and lipid profile. IR was measured quantitatively by a homeostatic model of assessment (HOMA-IR). Results: A total of 545 (28.2%) children with overweight/obese were included. Male:Female ratio was 1:1.27. The overall prevalence of metabolic syndrome (MS) in these children was 21.8%. Around 32.3% of children had HOMA-IR of ≥2.5, and 22.2% had HOMA-IR of ≥3.16. The mean HOMA-IR in children with MS was 5.46 compared to 2.18 in those without MS. An increased risk of IR with low HDL, high triglyceride, increased waist circumference, and increased BP (both systolic and diastolic) was found. This means, the insulin resistance was commoner in children with over-weight/obesity and underlying MS. Conclusions: The present school based study found a high prevalence of insulin resistance among children with over-weight/obesity. This could predict an increased risk of future adverse cardio-vascular events in the study children. The findings of this study would help in planning and implementing primary prevention programs targeting weight management and life-style change in the school going children.